2011
DOI: 10.1021/ml200104h
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Reactivity of a Potent Platinum–Acridine Hybrid Antitumor Agent

Abstract: The formation of unusual seven-membered, sterically overloaded chelates [Pt(en)(L/L´)](NO3)2 (4a/4b) from the corresponding potent hybrid antitumor agents [PtCl(en)(LH/L´H)](NO3)2 (3a/3b) is described, where en is ethane-1,2-diamine and L(H) and L´(H) are (protonated) N-(2-(acridin-9-ylamino)ethyl)-N-methylpropionimidamide and N-(2-(acridin-9-ylamino)ethyl)-N-methylacetimidamide, respectively. Compounds 3a and 3b inhibit H460 lung cancer cell proliferation with IC50 values of 12 ± 2 nM and 2.8 ± 0.3 nM, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…This was unexpected since it has previously been observed that addition of steric bulk in this part of the molecule results in a decrease in cytotoxicity. 11 Another critical trend observed across the entire data set is that the hybrids in which the platinum moiety is separated from the intercalator by an extended propylene linker ( m = 3 in 9 and 12 ) show greatly reduced cell kill potential. For instance, in NCI-H460, derivatives 3´ and 11 (with m = 2) are approximately 6 times more cytotoxic than compounds 9 and 12 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This was unexpected since it has previously been observed that addition of steric bulk in this part of the molecule results in a decrease in cytotoxicity. 11 Another critical trend observed across the entire data set is that the hybrids in which the platinum moiety is separated from the intercalator by an extended propylene linker ( m = 3 in 9 and 12 ) show greatly reduced cell kill potential. For instance, in NCI-H460, derivatives 3´ and 11 (with m = 2) are approximately 6 times more cytotoxic than compounds 9 and 12 .…”
Section: Resultsmentioning
confidence: 99%
“…11 These ligands proved to be extremely labile, which resulted in undesired intramolecular substitution of the oxygen donor by the 9-amino group of the acridine moiety to produce a substitution-inert, marginally cytotoxic nitrogen chelate. We reasoned that incorporation of the carboxylato ligand as a pendant group into a chelate, similar to the dicarboxylato leaving group in the clinical drug carboplatin, 1 should produce a more stable, but yet DNA reactive entity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, benzothiazole has been an attractive pharmacological scaffold present in anti-cancer drugs, such as phosphatidyl inositol inhibitor 23,24) it is reasonable to combine benzothiazole with rapamycin nucleus to form a single molecular framework. 25,26) Through above mentioned molecular hybridization and bioisosterism process, it will be possible to obtain novel rapamycin derivatives with better anti-cancer activity with increasing bioavailability and better pharmacokinetics properties.…”
mentioning
confidence: 99%